The Effect Of Transformational Leadership, Work Discipline And Competence On Employee Performance PT. Ice Cream Campina Surabaya - Akbar Dwi Permana Putra (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to determine the effect of Transfromational Leadership Style on, Work Discipline, and Competence on Employee Performance at PT. Campina Ice Cream Surabaya. This type of research uses a quantitative approach, where researchers distribute questionnaires as data retrieval media which are then processed into interval data which are then tested using the SPSS18 application. The population and samples in this study were 55 employees of PT. Campina Ice Cream Surabaya. The results of the simultaneous hypothesis test obtained F count value of 454,106 with a significant level of 0,000, there is a simultaneous significant effect between transfromational leadership style, work discipline, and competence towards employee performance. In partial hypothesis testing, work discipline variables that do not significantly influence employee performance. While the results of the determination test obtained simultaneously (R square) of 0.964 means that the variation in the value of Employee Performance is influenced by the Style of Transformational Leadership, Work Discipline, and Competence of 96.4% while the remaining 3.6% is influenced by other variables not examined.